Duodenal intraepithelial lymphocytosis is common in children without coeliac disease, and is not meaningfully influenced by Helicobacter pylori infection. Issue 11 (7th April 2014) - Guz‐Mark, A.; Zevit, N.; Morgenstern, S.; Shamir, R.
Summary Background Increased numbers of duodenal intraepithelial lymphocytes (IELs) characterise coeliac disease (CD) but have also been described in noncoeliacs. Controversy exists regarding an association between increased IELs and infection with Helicobacter pylori, which is commonly found in children. Aim To assess the relationship between H. pylori infection and duodenal IELs in a large cohort of children, with and without CD. Methods We reviewed gastric and duodenal biopsies of children who underwent esophagogastroduodenoscopy between January 2006 and February 2013 because of either recurrent abdominal pain (RAP) or suspected CD at Schneider Children's Medical Center of Israel, a referral centre for Israel's largest Health Maintenance Organization. The duodenal IEL count and H. pylori presence in antral biopsies were determined for each specimen. Results Children with RAP (n = 693) or CD (n = 306) were included. Among children with RAP, H. pylori was present in 33.8%. The mean IEL count in the H. pylori positive RAP group was 17.8(±8.8)/100 enterocytes, vs. 15.8(±8.3) in the H. pylori negative patients (P = 0.004). Increased IEL counts (≥25 IELs/100 enterocytes) were found in 15.7% of H. pylori negative, noncoeliac children. Among children with CD, there was no significant difference in IEL counts according to H. pylori status: 73.1(±26.1) vs. 72.6 (±26.5) in H. pylori positive and negative patients respectively. Conclusions Our study suggests that slightly elevated duodenal intraepithelial lymphocyte counts are common in the paediatric population. Helicobacter pylori infection has no major influence on the intraepithelial lymphocyte counts in children with recurrent abdominal pain or children with coeliac disease.